Evaluating moisture damage resistance in asphalt mixtures using amine-free anti-stripping agent for enhanced durability - Abdulaziz Muhmood, Abdulbasit; Al-Saffar, Zaid Hazim; Dulaimi, Anmar; Haryati, Yaacob; A. Al-Attar, Alyaa; Putra Jaya, Ramadhansyah; Bilema, Munder (Springer, 2025)
Moisture-induced durability and strength loss are major concerns in asphalt mixtures. Traditional additives often suffer from environmental concerns or inconsistent performance, highlighting the need for sustainable alternatives. This study evaluates an eco-friendly, amine-free anti-stripping additive designed to enhance binder-aggregate adhesion and maintain stable performance across different materials. Moisture resistance was assessed using indirect tensile strength (ITS), tensile strength ratio (TSR), boiling tests, Marshall immersion, and MATLAB-based image analysis. The additive significantly improved adhesion, between the asphalt binder and aggregates, as evidenced by the tensile strength ratio (TSR) values of 95% and 74% after 24 h and 48 h of conditioning, respectively. Additionally, stability was improved, with treated unconditioned samples exhibiting a peak value of 15.6 kN, compared to 13.72 kN for the untreated samples. Upon immersion for 24 h, stability in the treated mixtures decreased by only 3.2%, in contrast to a decline of 11% in the untreated mixtures. This reduction in stability can be attributed to the diminished adhesive properties between the aggregates and binder caused by prolonged exposure to heat and moisture. The findings underline the additive’s effectiveness in enhancing both moisture resistance and mechanical performance, thereby demonstrating its potential for improving the durability and sustainability of asphalt pavements.